1996
DOI: 10.1016/0003-4878(95)00060-7
|View full text |Cite
|
Sign up to set email alerts
|

Air movement around a worker in a low-speed flow field

Abstract: A knowledge of the air movement around a worker in a low-speed airflow is important in a number of areas: containment testing of fume cupboards; testing of personal dust samplers; testing of LEV effectiveness; and measurement of worker exposure. Measurements of velocity vectors around the upper torsos of manikins and a human in low-speed airflows have been made using a laser Doppler anemometer. Both heated and unheated manikins, as well as a 'breathing' manikin were used. The results show that quite distinctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 3 publications
3
27
1
Order By: Relevance
“…These factors will determine the extent of disturbance that invading flow exerts over the human natural convection flow. Similar study performed in a low-speed uniform environment revealed that heated and non-heated manikin creates very distinctive airflow patterns with respect to the free air stream (Johnson et al, 1996). An airflow of 6 l/s supplied from the front was able to penetrate the CBL, while personalized jet at the lower flow rate was deflected upwards by the CBL without reaching the breathing zone.…”
Section: Introductionmentioning
confidence: 55%
“…These factors will determine the extent of disturbance that invading flow exerts over the human natural convection flow. Similar study performed in a low-speed uniform environment revealed that heated and non-heated manikin creates very distinctive airflow patterns with respect to the free air stream (Johnson et al, 1996). An airflow of 6 l/s supplied from the front was able to penetrate the CBL, while personalized jet at the lower flow rate was deflected upwards by the CBL without reaching the breathing zone.…”
Section: Introductionmentioning
confidence: 55%
“…Bjørn and Nielsen [5] and Johnson et al [7] found that buoyant upward flow in the vicinity of an occupant affects pollutant dispersion in breathing zone. The effect of the buoyant thermal plume becomes significant in a space with little or no air mixing, such as a space in which a mechanical ventilation system is not operating or a room with displacement ventilation [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…Some existing studies have investigated the interaction between the thermal plume and indoor ventilation. Johnson et al (1996) studied airflow interaction between the human free convection flow and ventilation in a low-speed uniform environment. Yang et al (2009a) studied the interaction of the personalized airflow supplied from ceiling mounted nozzle with the thermal plume generated by a seated thermal manikin.…”
Section: Introductionmentioning
confidence: 99%